2002
DOI: 10.1034/j.1399-0039.2002.590605.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of the HLA‐A*19 group of alleles in North Indians: Possible oriental influence

Abstract: The present study aims to determine the genetic diversity of the HLA-A19 allelic family in the North Indian and Japanese populations. The HLA-A*19 group of alleles occurred at similar frequencies in North Indians and Japanese as in Caucasians. All the known serological splits of HLA-A19 were observed among the North Indians, i.e. A*33 (15.6%), A*32 (8.6%), A*31 (3.5%), A*30 (3%), A*29 (1.2%) and A*74 (0.77%), while only A*30 (0.7%), A*31 (17.6%) and A*33 (11.7%) were observed in the Japanese. High resolution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…High-resolution analysis of polymorphic HLA antigens, such as HLA-A2 [26] and HLA-A19 [27], in the healthy north Indian population revealed mixed representation of white and Asian alleles in this population, with the presence of some novel specificities, such as A*0211 and A*3306. Despite this, sequence analysis of amino acid residues constituting the peptide-binding pockets B and F in the observed molecular subtypes of A*02, A*30, A*31, A*32, and A*33 alleles suggests a sequence motif similar to that found in their corresponding HLA supertypes.…”
Section: Discussionmentioning
confidence: 86%
“…High-resolution analysis of polymorphic HLA antigens, such as HLA-A2 [26] and HLA-A19 [27], in the healthy north Indian population revealed mixed representation of white and Asian alleles in this population, with the presence of some novel specificities, such as A*0211 and A*3306. Despite this, sequence analysis of amino acid residues constituting the peptide-binding pockets B and F in the observed molecular subtypes of A*02, A*30, A*31, A*32, and A*33 alleles suggests a sequence motif similar to that found in their corresponding HLA supertypes.…”
Section: Discussionmentioning
confidence: 86%
“…The frequency of HLA‐A*33 and HLA‐A*32 was 21.5% and 4.5% in western Indians (Shankarkumar et al ., 2002), 18% and 10.2% in Asian Indians (Mehra et al ., 2001) and 15.6% and 8.6% in North Indians (Jaini et al ., 2002). However, Pathans, Sindhi and Punjabis have reported low frequency of 7.8% and 2.6%, 9.2% and 4.4%, and 13.9% and 4.4%, respectively (Clayton et al ., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Low frequencies of 2.6% and 2.7% have been reported in Pathans (Clayton et al ., 1997) and Asian Indians (Mehra et al ., 2001), respectively. However, a frequency of 3.5%, 4% and 8.8% have been reported in North Indian (Jaini et al ., 2002), Sindhi (Clayton et al ., 1997) and western Indian populations (Shankarkumar et al ., 2002), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Distribution of HLA-A, B, DRB 1 serological equivalents across different populations, mainly Caucasians in the West, Orientals in the east, with black populations and the North Indians forming a transition zone between the east and the west, reveal four patterns of allele frequency distributions. Allele frequencies either (Jaini et al 2002a) The North Indian MHC repertoire has revealed interesting results on analysis of the allele distribution maps. The population shows allele frequencies intermediate to those seen in major ethnic groups located to the east and the west of the subcontinent.…”
Section: Inter-population Variability Of Mhe Genesmentioning
confidence: 99%